METODE BERBICARA DALAM MENINGKATKAN KEMAMPUAN BERBICARA DAN MOTIVASI BELAJAR - Rindaningsih, Ida; Alfaini, Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main objectives in this study are to determine the effect of storytelling method on speaking ability, to determine the effect of storytelling method on learning motivation and to determine the effect of speaking ability on learning motivation. The type of research used in this study is explanatory research with a quantitative approach. The sample in the study amounted to 22 students and was a saturated sample. Data analysis in this study used descriptive analysis and path analysis. To analyze the data using the SPSS version 16.0 for windows program. Based on the results of path analysis, it shows that the story method variable (X) has a significant influence on speaking ability (Y1) with a value of 0.000. The variable of storytelling method (X) has a significant influence on learning motivation (Y2) with a value of 0.002. speaking ability (Y1) has a significant influence on learning motivation (Y2) with a value of 0.000.